PEMANFAATAN PLATFORM METAVERSE UNTUK VISUALISASI PERENCANAAN PARIWISATA PESISIR TERINTEGRASI - Atmojo, Wahyu Tisno; Olivia, Deasy; Ayunda, Afifah Trista (STMIK Sinar Nusantara, 2026)
Using immersive technology in regional planning is now essential to provide an accurate picture of how areas will develop in the future. This study aims to design and develop a Virtual Reality (VR) Tour application that visualizes the integrated coastal tourism plan in Tangerang Regency. The coastal area of Tangerang has a lot of potential but needs more interactive social media communication to involve stakeholders and the community in planning. The development method used is the Multimedia Development Life Cycle (MDLC), which consists of six stages: concept, design, collecting materials, assembly, testing, and distribution. The development was done using Roblox Studio because of its strengths in rendering multi-user environments and the ease of access across different devices. The result of this research is a VR application that allows users to explore a digital prototype of the tourism area, including infrastructure facilities and mangrove conservation areas, in an immersive way. Testing the app showed that using VR devices gives a more detailed spatial experience compared to traditional models or 2D maps. This study concludes that using Roblox Studio with the MDLC method is effective in speeding up the process of creating VR prototypes for coastal tourism planning that is both communicative and educational.